The selection of a hydrophobic 7-phenylbutyl-7-deazaadenine-modified DNA aptamer with high binding affinity for the Heat Shock Protein 70 - Mulholland, Catherine; Jestřábová, Ivana; Sett, Arghya; Ondruš, Marek; Sýkorová, Veronika; Manzanares, C Lorena; Šimončík, Oliver; Muller, Petr; Hocek, Michal (Communications chemistry, 2023)
Nucleic acids aptamers often fail to efficiently target some proteins because of the hydrophilic character of the natural nucleotides. Here we present hydrophobic 7-phenylbutyl-7-deaadenine-modified DNA aptamers against the Heat Shock Protein 70 that were selected via PEX and magnetic bead-based SELEX. After 9 rounds of selection, the pool was sequenced and a number of candidates were identified. Following initial screening, two modified aptamers were chemically synthesised in-house and their binding affinity analysed by two methods, bio-layer interferometry and fluorescent-plate-based binding assay. The binding affinities of the modified aptamers were compared with that of their natural counterparts. The resulting modified aptamers bound with higher affinity (low nanomolar range) to the Hsp70 than their natural sequence (>5 µM) and hence have potential for applications and further development towards Hsp70 diagnostics or even therapeutics.